MENINGKATKAN MOTIVASI BELAJAR ANAK MELALUI PEM-BERIAN BINTANG PRESTASI DI KOBER MUTIARA ILMU - Lela Sari; Rohmalina Rohmalina (IKIP Siliwangi, 2022)
This research was conducted based on finding problems that arise in the school environment, especially in early childhood education, which are related to children's learning motivation. This is evident in schools that show some children who show a lack of enthusiasm and even do not want to take part in the learning process, for example, children are not yet active in participating in activities before and after praying, do not pay attention to the teacher's explanations, and do not do the assignments given. This problem demands the need for an interesting approach, method, and learning media to deal with these problems, one of which is the awarding of Achievement Stars. The method used is a qualitative descriptive method that aims to describe the increase in children's learning motivation. This study involved 10 children aged 5-6 years. Data were collected through observation, interviews, and documentation. The data analysis used is data reduction, data presentation, and conclusions or data verification. Based on the analysis of previous research data, it was found that before the awarding of this achievement star, the children were less enthusiastic about participating in learning activities. The results showed that the awarding of Achievement Stars could motivate children's learning. For example, children are enthusiastic about learning and become accustomed to praying without being asked first, to do the tasks given by the teacher until they are finished. By giving this achievement star, educators are helped so that they can increase children's learning motivation.Penelitian ini dilakukan atas dasar temuan masalah yang muncul dalam lingkungan sekolah khususnya pada pendidikan anak usia dini, yaitu terkait dengan motivasi belajar anak. Hal ini terbukti di sekolah terlihat beberapa anak yang menunjukkan kurang semangat bahkan tidak mau mengikuti proses pembelajaran, misalnya anak belum aktif dalam mengikuti kegiatan sebelum dan sesudah berdoa, tidak memperhatikan penjelasan guru, dan tidak mengerjakan tugas yang diberikan. Permasalahan ini menuntut perlunya suatu pendekatan, metode dan media pembelajaran yang menarik untuk menangani masalah tersebut salah satunya dengan pemberian Bintang Prestasi. Metode yang digunakan adalah metode deskriptif kualitatif yang bertujuan untuk menggambarkan peningkatan motivasi belajar anak. Penelitian ini melibatkan anak usia 5-6 tahun yang berjumlah 10 orang. Data dikumpulkan melalui observasi,wawancara dan dokumentasi. Analisis data yang digunakan yaitu reduksi data, penyajian data dan kesimpulan atau verifikasi data. Berdasarkan analisis data penelitian sebelumnya diperoleh bahwa sebelum adanya pemberian bintang prestasi ini anak kurang semangat dalam mengikuti kegiatan pembelajaran. Hasil penelitian menunjukkan bahwa melalui pemberian Bintang Prestasi, dapat memotivasi belajar anak. Misalnya anak semangat dalam belajar, menjadi terbiasa melakukan kegiatan berdoa tanpa disuruh terlebih dahulu, mengerjakan tugas yang diberikan guru sampai selesai. Dengan adanya pemberian bintang prestasi ini pendidik terbantu sehingga dapat meningkatkan motivasi belajar anak.